Do coaches perceive themselves differently from physical education teachers on athletic identity and motivation? - Almeda-Estanislao, Susan R. (Philippine Journal of Counseling Psychology, 2005)
This paper examined the self-perceived psychological components of "being athletic" that differentiate coaches from physical education (PE) teachers. Further, it sought to find out if coaches are better motivated than PE teachers in terms of their involvement in exercise, sports and physical activities in certain fashions. Sixty four (64) coaches and PE teachers responded to the Athletic Identity Questionnaire, the Situational Motivation Scale and two open-ended questions. Results revealed that both groups positively identified themselves as athletic and are intrinsically and extrinsic ally motivated in engaging in exercises, sports and physical activities. However, PE teachers were found to lack conmpetence or control and place little value on sports or a particular physical activity in comparison to coaches.